2011
DOI: 10.1007/s10584-011-0338-8
|View full text |Cite
|
Sign up to set email alerts
|

A regional comparison of the effects of climate change on agricultural crops in Europe

Abstract: The effects of climate change will be felt by most farmers in Europe over the next decades. This study provides consistent results of the impact of climate change on arable agriculture in Europe by using high resolution climate data, socio-economic data, and impact assessment models, including farmer adaptation. All scenarios are consistent with the spatial distribution of effects, exacerbating regional disparities and current vulnerability to climate. Since the results assume no restrictions on the use of wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 46 publications
2
75
0
9
Order By: Relevance
“…According to previous literature, the losses produced by drought conditions are crop-specific and they depend on location. The same can be shown in this analysis (Parry et al, 2004;Iglesias et al, 2012a;Lobell et al, 2008). The climate-change-induced and drought-induced losses in physical yields (t h −1 ) have been largely analysed in the literature, and they are expected to be very high for some of the crops analysed here, especially in the southern and eastern regions in Spain.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…According to previous literature, the losses produced by drought conditions are crop-specific and they depend on location. The same can be shown in this analysis (Parry et al, 2004;Iglesias et al, 2012a;Lobell et al, 2008). The climate-change-induced and drought-induced losses in physical yields (t h −1 ) have been largely analysed in the literature, and they are expected to be very high for some of the crops analysed here, especially in the southern and eastern regions in Spain.…”
Section: Discussionsupporting
confidence: 75%
“…We have found that the differences in terms of income distribution are not as severe as those reported in studies that analyse solely physical impacts , which suggests an important role of market prices in stabilizing farmers' outcomes. Although most of the studies project important crop production to be reduced due to climate change in Spain (Iglesias et al, 2012a;López-Gunn et al, 2012), our results could imply rural incomes not suffering the most through agriculture losses but consumers' welfare being the most greatly affected. We have not analysed consumers' welfare here directly.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Climate models predict that such a growing tendency could not only continue but also influence other climate variables, such as frost and rainfall (IPCC, 2013). The close relationship between climate and agriculture makes agriculture particularly sensitive to the potential impacts of climate change (Moriondo et al, 2010;Iglesias et al, 2012). Climate change may lead to modifications in cropping patterns, crop water requirements and, among others, the seasonal distribution of water demand.…”
Section: Introductionmentioning
confidence: 99%